Analisis Isi Mengenai Cara Mengenali Diri Sendiri Dalam Podcast Suara Berkelas Pada Platform Youtube - Risti Septyani; Fadiah Cahya Amelia; Ika Choirunnissa; Mario Maulana; April Laksana (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
Using a qualitative research methodology, this study investigated the concept og self-recognition. The aim of the research was to understand how people can use the principles of Human Design to see discover on one’s life experiences, social interactions, and cultural context cal help them understand themlelves better. Important insights into human-based therapies and self-development are given in this classyvoices podcast. A system that combines elements of astrology, genetics, kabbalah, and the I Ching to provide insight into one’s personality and potential is known as a Human Design. According to research, people who have a good understanding of themselves tend to be better at managing their emotions dealing with stress, and living a more genuine life.